Analysis of Occupational Safety and Health Risk in Emergency Installations with Hospital X Yogyakarta Using The Failure Mode Effect and Analysis (FMEA) Method - Muchamad Rifai; Noer Ayu Purnatimur (Dental and Oral Hospital of Universitas Muhammadiyah Semarang, 2023)
Background: Risk management of occupational safety and health in hospital can be used to limit, minimize, and eliminate hazards in hospitals. While the emergency department is the major service for emergency patients, there is a significant risk of five hospital components, including health professionals, patients, patient families, visitors, and the environment, because of X Hospital Yogyakarta has developed a risk management program. The goal of this study was to analyze the risk of occupational safety and health in X hospital Yogyakarta emergency department. Method: This research employs a qualitative approach using form Failure Mode Effect and Analysis (FMEA). Direct observation and conducting in depth interviews with informants are two methods for gathering data. The research carried out in and covered all work activities at X Hospital emergency department. Result: There are 21 work activities with recognized OSH concerns, with 4 work activities having a high risk level, 8 work activities having a potential risk , and 9 work activities having a torelable risk. Taking anamnesis, blood sampling, patient examination, patient admission, and medical acts using sharp instruments are the most common sources of danger; there have been incidents in the emergency department cause medical action with sharp tools resulted in cases of like needle stick injuries to health workers hit by broken glass ampoules and so on. Conclusion: The implementation occupational health and safety culture, can influence worker behavior in order to reduce the number of errors and infractions, as well as the likelihood of work accidents occurring again.